2008
DOI: 10.1021/ef700704n
|View full text |Cite
|
Sign up to set email alerts
|

Gasification of New Zealand Coals: A Comparative Simulation Study

Abstract: The aim of this study was to conduct a preliminary feasibility assessment of gasification of New Zealand (NZ) lignite and sub-bituminous coals, using a commercial simulation tool. Gasification of these coals was simulated in an integrated gasification combined cycle (IGCC) application and associated preliminary economics compared. A simple method of coal characterization was developed for simulation purposes. The carbon, hydrogen, and oxygen content of the coal was represented by a three component vapor solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…For the calculation a pressurised, oxygen-fed, entrained flow gasifier (based on Shell technology, (Cormos, 2012;Maustrad, 2005;Smitha et al, 2008;Sun et al, 2011;Zheng and Furinsky, 2005)), powered with coal with the composition shown in Table 1 was chosen.…”
Section: Description Of Igcc Systemmentioning
confidence: 99%
“…For the calculation a pressurised, oxygen-fed, entrained flow gasifier (based on Shell technology, (Cormos, 2012;Maustrad, 2005;Smitha et al, 2008;Sun et al, 2011;Zheng and Furinsky, 2005)), powered with coal with the composition shown in Table 1 was chosen.…”
Section: Description Of Igcc Systemmentioning
confidence: 99%
“…Gibb's equilibrium models, such as those found in [21,29,30], which use a general equilibrium model, without pre-specified reactions. Kinetic and mass transfer models.…”
Section: Gasifier Modelingmentioning
confidence: 99%
“…Liquid sulphur is recovered from reactor outlets using two phase flash units to model the liquid vapor separations. Gas reactor outlets are fed to a series of two equilibrium reactors, which constitute the catalytic stages represented by the chemical reactions (24), (30) and (31). The hydrogenation step takes place in a conversion reactor that considers S 2 and SO 2 conversion into H 2 S (see Eqs.…”
Section: 224mentioning
confidence: 99%
“…In the efficiency improvement study, gasification can be employed to combine IGCC with solid oxide fuel cell (SOFC), convert solid fuel to liquid fuel, or produce electricity and chemical products simultaneously . Although the gasification phenomena are complicated to get exact simulation, it is reasonable to simulate final gas compositions with gasification reactions under higher temperature by employing ideal thermodynamics in system‐level simulation models …”
Section: Introductionmentioning
confidence: 99%